Environmental DNA methods for detecting two invasive alien species (American bullfrog and red swamp crayfish) in Japanese ponds. Issue 6 (5th July 2022) - Ogata, Shigeki; Doi, Hideyuki; Igawa, Takeshi; Komaki, Shohei; Takahara, Teruhiko
Abstract: Species invasion in conventional ecosystems is an impedance to ecosystem management. The extensive invasion of American bullfrogs ( Lithobates catesbeiana ) and red swamp crayfish ( Procambarus clarkii ) is seriously harmful to aquatic systems worldwide, including Japan. In recent years, the methods involving environmental DNA (eDNA) have significantly contributed to the detection of invasive alien species. These methods for the above two species had already been developed in previous studies overseas, but could be unsuitable for detection of the species in Japan due to matching of the polymerase chain reaction (PCR) primers with the sequence of the co‐existing species. The present study developed two eDNA detection methods for L. catesbeiana and P. clarkii in Japanese habitats. The eDNA of both invasive alien species was detected in all ponds where they had been captured and observed. A positive relationship was elucidated between the traditional survey (i.e., frog male calling detection or direct catch) and the presence or concentration of eDNA. The eDNA method applied in this study could be useful for monitoring the distribution of L. catesbeiana and P. clarkii in Japan. Abstract : We developed the new two eDNA detection systems, which can be used to obtain quick and accurate responses for understanding the distribution of both American bullfrog Lithobates catesbeiana and red swamp crayfish Procambarus clarkii in Japanese ponds.